Model Networking Kemitraan Untuk Peningkatan Daya Saing Agribisnis Umbi Porang di Kecamatan Pattalassang Kabupaten Gowa - ASRIADI, ANDI AMRAN; HUSAIN, NAILAH; RAHMAWATI, RAHMAWATI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.3, Desember 2020, 2020)
Partnership Networking Model For Improvement  Competitiveness Agribusiness Porang Tuber In The District Pattalassang Gowa District Partnership is a business strategy carried out by two or more parties within a certain period of time to achieve mutual benefit. In this relation, in running a partnership with partner farmers, aimed to get the maximum possible profit and be sustainable. This study aimed: 1) to determine a partnership networking model in improving porang tuber agribusiness in Pattalassang District, Gowa Regency that had been developed. 2). to determine the networking relationship between upstream-downstream stakeholders on the competitiveness of porang tuber agribusiness in Pattalassang District, Was regency which had been developed. The method used in this research was simple random sampling. The data used were primary and secondary data which were analyzed descriptively-qualitatively and quantitatively. The results showed that one of the partnership models between the Village Government, the sub-district, traders, warehouses and farmers was a partnership between farmers in Pattalassang District, Gowa Regency, to collaborate between a buying partner. The partial correlation relationship of upstream networking, farmer partnerships, the relationship between the distribution of inputs to seeds, fertilizers and medicines had a significant effect on partnerships to determine price competitiveness, quality, determination of types and quantities, and timeliness of market availability. Meanwhile, the partial correlation relationship, downstream networking, partnership, the relationship between farmers and collectors had a significant effect on the determination of price competitiveness, quality, determination of types and quantities, and the timing of market availability. The farmer partnership with the warehouse had a significant effect on the determination of price competitiveness, quality, determination of type and quantity, and timeliness of market availability. The partnership of farmers with the processing industry had a significant effect on the determination of price competitiveness, quality, determination of types and quantities, and timeliness of market availability.